Über die Herkunft der Frau des Mose - Gerhards, Meik (Vetus Testamentum, 2005)
The quest for the historical Moses has to start from two motifs in the biblical account, which are not deducible from the interests of later times, i.e., the Egyptian name of Moses and his non-Israelite wife. Concerning the latter motif the Old Testament account includes three versions about the origin of the woman (Midianite, Cushite, Qenite). The paper wants to show, how these differences could be explained as variations of an originally unique information, so that they can be taken as an indication of the long tradition the motif has undergone. The two non-deducible motifs indicate that the historical Moses was indeed the leader of the Exodus as well as the mediator of the revelation of Yahweh.